2023
DOI: 10.3389/fpsyt.2022.960055
|View full text |Cite
|
Sign up to set email alerts
|

The structural model of cyberchondria based on personality traits, health-related metacognition, cognitive bias, and emotion dysregulation

Abstract: IntroductionCyberchondria is excessive seeking for online health-related information related to increasing health anxiety and distress levels. The current study investigated the mediating role of health-related metacognition, cognitive bias, and emotion dysregulation in the relationship between personality traits and cyberchondria.MethodsParticipants were 703 individuals 18+ years old who had access to the internet (males = 43.8%, mean age = 33.82 ± 10.09 years and females = 56.2%, mean age = 34.37 ± 11.16 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 106 publications
(142 reference statements)
0
1
0
Order By: Relevance
“…Also, the present findings indicate that extraversion is associated with delayed dental visits or other unhealthy behavior because of the passage through conscientiousness. Extraversion has been reported to be related to positive aspects such as coping with stress [ 24 ], while other studies have found that extraversion may be influenced by aspects of emotional impulsivity [ 25 ] and unrealistic optimism [ 26 ], and that it is more likely to lead to underestimation of the risk of illness [ 27 ]. There is a possibility that such characteristics of extraversion might have led to the present results.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the present findings indicate that extraversion is associated with delayed dental visits or other unhealthy behavior because of the passage through conscientiousness. Extraversion has been reported to be related to positive aspects such as coping with stress [ 24 ], while other studies have found that extraversion may be influenced by aspects of emotional impulsivity [ 25 ] and unrealistic optimism [ 26 ], and that it is more likely to lead to underestimation of the risk of illness [ 27 ]. There is a possibility that such characteristics of extraversion might have led to the present results.…”
Section: Discussionmentioning
confidence: 99%